Analisis Pengaruh Profitabilitas, Liquidity, Dan Fixed Tangible Assets Terhadap Leverage Perusahaan - Mafvaza Fitria Nurcholis; Mulyani Mulyani (Peneliti.net, 2023)
This study aims to analyze the effect of profitability, liquidity, and fixed tangible assets on company leverage. Case studies were conducted on companies listed on the Indonesia Stock Exchange. The research uses a quantitative approach by collecting secondary data on company financial reports available on the Indonesia Stock Exchange's website. The number of samples used in this study were 34 samples using a purposive sampling technique. The data analysis technique used is multiple linear regression analysis, individual t hypothesis testing and simultaneous hypothesis testing F. The results show that: (1) profitability has a negative and significant effect on leverage individually; (2) liquidity has a negative and significant effect on leverage individually; (3) fixed tangible assets have a negative and significant effect on leverage individually; (4) profitability, liquidity, and fixed tangible assets have a negative and significant effect on leverage simultaneously.